Structure and nucleic-acid binding of the Drosophila Argonaute 2 PAZ domain. - Lingel, A.; Simon, B.; Izaurralde, E.; Sattler, M. (Nature, 2003)
RNA interference is a conserved mechanism that regulates gene expression in response to the presence of double-stranded (ds)RNAs. The RNase III-like enzyme Dicer first cleaves dsRNA into 21-23-nucleotide small interfering RNAs (siRNAs). In the effector step, the multimeric RNA-induced silencing complex (RISC) identifies messenger RNAs homologous to the siRNAs and promotes their degradation. The Argonaute 2 protein (Ago2) is a critical component of RISC. Both Argonaute and Dicer family proteins contain a common PAZ domain whose function is unknown. Here we present the three-dimensional nuclear magnetic resonance structure of the Drosophila melanogaster Ago2 PAZ domain. This domain adopts a nucleic-acid-binding fold that is stabilized by conserved hydrophobic residues. The nucleic-acid-binding patch is located in a cleft between the surface of a central beta-barrel and a conserved module comprising strands beta3, beta4 and helix alpha3. Because critical structural residues and the binding surface are conserved, we suggest that PAZ domains in all members of the Argonaute and Dicer families adopt a similar fold with nucleic-acid binding function, and that this plays an important part in gene silencing.